Study of independent diagnostic efficacy and co-diagnostic strategies of molecular markers for diabetic cardiomyopathy - Su, Na; Zhao, Jingxuan; Zhang, Weiyi; Zhang, Xinhuan; Lu, Kunna; Ma, Yan; Wang, Yan; Cao, Mingfeng (Frontiers in Endocrinology, 2025)
Word count of the full article: 4834Diabetic cardiomyopathy (DCM) is defined as myocardial dysfunction in diabetes mellitus (DM) patients independent of coronary artery disease (CAD) or hypertension (HTN). With high morbidity and mortality, DCM poses a significant threat to patient health. Its underlying pathogenesis remains incompletely elucidated, and the prolonged subclinical phase renders early diagnosis and precise treatment clinically challenging. Thus, identifying viable biomarkers for early diagnosis and intervention has emerged as a research imperative, whereas a systematic DCM diagnostic and therapeutic strategy remains to be established. Our examination revealed that circulating soluble suppression of tumorigenicity 2 (sST2), Cardiotrophin-1 (CT-1), and galectin-3 levels correlate closely with DCM progression stages. Combining Lysyl Oxidase-Like 2 (LOXL2) and Electron Transfer Flavoprotein β Subunit (ETFβ) measurements with ultrasound E/E’ ratio and NT-proBNP enhances diagnostic accuracy. Novel noninvasive markers (e.g., skin autofluorescence) show promise. This article comprehensively evaluates the clinical applications of these molecular markers within DCM’s pathophysiological classification framework.